Tipos de secagem no rendimento industrial de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Reception and drying structure are an obstacle in the paddy rice production flow, therefore the practice of staggered drying is common until the structure is available for a complementary drying. The purpose of this work was to evaluate the influence of complete and staggered drying on rice yield. Three cultivars of paddy rice were collected, cleaned, homogenized and divided by quartering. The samples were dried in a test dryer, half up to 13% moisture (complete drying) and another half up to 16% (staggered drying), which after 30 days was again dried at 13% moisture. After 90 and 120 days of drying, the samples were processed in a rice tester and the yields were determined. Amongst the analyzed cultivars, BR-IRGA 409 and IRGA 424 presented higher yields of whole grains and milling. Complete drying provided higher whole grain yields for the BR-IRGA 409 and IRGA 424 cultivars, lower output of broken grains for BR-IRGA 409 and superior yield turnout for IRGA 424. The yields of PUITÁ INTA CL were not influenced by the type of drying, however they were inferior to the others cultivars. The results suggest that staggered drying is detrimental to the integrity of rice grains.
Keywords: Oryza sativa; Umidade; Secagem escalonada; Beneficiamento; Grãos inteiros; Humidity; Staggered drying; Processing; Whole grains; CNPQ::CIENCIAS AGRARIAS